Skyddsområde för Rörbäcks grundvattentäkt : Med Riskanalys och förslag på sekundärt skyddsområde - Olsson, Anders (2011)
This thesis work was the final step in the Samhällsbyggnadsprogrammet 120 hp at LTU. It was produced as part of the Environmental Management course for the Department of Technical Supply in Kalix Municipality, Norrbotten. Aim of the thesis is to examine the risks of pollution from private sewages which unfortunately often provide inadequate filtering of waste water, compared to municipal water and wastewater systems. The area in question lies in Rörbäck, northeast of Luleå. Kalix municipality is the responsible authority of drinking water in the area, but Luleå municipality owns the land not covered by the water pit and groundwater well area. Stricter rules of the EU Water Framework Directive have created a need to develop procedures for maintaining secure water quality and eliminate potential risks associated with water contamination. Previous to this work, a survey has been sent to property owners to inquire about their individual sewage systems in order to gain an understanding of the present situation. This thesis consists essentially of two parts. The first discusses and analyzes the probability of infiltration in the soil in the area based on topographic, geological and geo-hydrological information, and the second is an analysis of general contaminant risks. Also an estimate of the well area boundaries is provided, calculated according to standards set by the Protection Agency as stated in the agency manuals (2003:6). Topographical maps with elevation lines have been used to determine the slope and likely catchment area of aquifers, based on the variation in the terrain in the ground and its gradient. Geological soil maps, together with geo-hydrological map information, were used to assess the probable extent of soil infiltration and location of the topography. The second part consists of a general risk analysis, which includes activities in the Rörbäck area and associated risk sources. The risk analysis examines the individual sewage treatment placements and their potential impact of pollution on the ...